Amorphous, Carbonated Calcium Phosphate and Biopolymer-Composite-Coated Si3N4/MWCNTs as Potential Novel Implant Materials - Furko, Monika; Detsch, Rainer; Horváth, Zsolt E.; Balázsi, Katalin; Boccaccini, Aldo R.; Balázsi, Csaba (Nanomaterials, 2024)
A biodegradable amorphous carbonated calcium phosphate (caCP)-incorporated polycaprolactone (PCL) composite layer was successfully deposited by a spin coater. In this specific coating, the PCL acts as a bioadhesive, since it provides a better adherence of the coatings to the substrate compared to powder coatings. The caCP–PCL coatings were deposited and formed thin layers on the surface of a Si3N4–3 wt% MWCNT (multiwalled carbon nanotube) substrate, which is an emerging type of implant material in the biomedical field. The composite coatings were examined regarding their morphology, structure and biological performance. The biocompatibility of the samples was tested in vitro with MC3T3-E1 preosteoblast cells. Owing to the caCP–PCL thin layer, the cell viability values were considerably increased compared to the substrate material. The ALP and LDH tests showed numerous living cells on the investrigated coatings. The morphology of the MC3T3-E1 cells was examined by fluorescent staining (calcein and DAPI) and scanning electron microscopy, both of which revealed a well-spread, adhered and confluent monolayer of cells. All performed biocompatibility tests were positive and indicated the applicability of the deposited thin composite layers as possible candidates for orthopaedic implants for an extended period.
CRIS-Team Scopus Importer:2024-02-16
Keywords: amorphous calcium phosphate; biocomposites; biopolymers; MWCNT; Si